An assessment of the ship drag penalty arising from light calcareous tubeworm fouling. Issue 4 (20th April 2016) - Monty, J. P.; Dogan, E.; Hanson, R.; Scardino, A. J.; Ganapathisubramani, B.; Hutchins, N.
Abstract: A test coupon coated with light calcareous tubeworm fouling was scanned, scaled and reproduced for wind-tunnel testing to determine the equivalent sand grain roughness k s . It was found that this surface had a k s = 0.325 mm, substantially less than the previously reported values for light calcareous fouling. This result was used to predict the drag on a fouled full scale ship. To achieve this, a modified method for predicting the total drag of a spatially developing turbulent boundary layer (TBL), such as that on the hull of a ship, is presented. The method numerically integrates the skin friction over the length of the boundary layer, assuming an analytical form for the mean velocity profile of the TBL. The velocity profile contains the roughness (fouling) information, such that the prediction requires only an input of k s, the free-stream velocity (ship speed), the kinematic viscosity and the length of the boundary layer (the hull length). Using the equivalent sandgrain roughness height determined from experiments, a FFG-7 Oliver Perry class frigate is predicted to experience a 23% increase in total resistance at cruise, if its hull is coated in light calcareous tubeworm fouling. A similarly fouled very large crude carrier would experience a 34% increase in total resistance at cruise.